A general approach to multicomponent metal-decorated crumpled reduced graphene oxide nanocomposites using a flame-based process. Issue 41 (8th October 2019) - Mohammadi, Mohammad Moein; Shao, Shikuan; Srivatsa Gunturi, Santosh; Raghavan, Anirudh Ravi; Alexander, Naveshkaanth; Liu, Yang; Stafford, Christopher M.; Buchner, Raymond D.; Swihart, Mark T.
Abstract : This manuscript presents a new single-step flame route to making multicomponent metal-decorated crumpled reduced graphene oxide balls. Abstract : We introduce a general approach for synthesizing multicomponent metal-decorated crumpled reduced graphene oxide nanocomposites using a one-step, continuous flame-based process. Crumpled reduced graphene oxide balls (CGB) were produced from graphene oxide (GO) in a High Temperature Reducing Jet (HTRJ) reactor. Moreover, CGBs were simultaneously decorated with different transition metal nanoparticles, including cobalt (Co), nickel (Ni), iron (Fe), and palladium (Pd). Various metal alloy-decorated crumpled reduced graphene oxide balls (M-CGBs) including CoPd-, CoNi-, CoPdNi-, and CoNiFe-CGBs were successfully synthesized using a general recipe. The key advantage of the HTRJ system over common flame-based aerosol synthesis methods is the separation of flame and product formation zones, which allows production and/or reduction of nanomaterials that can be reduced by H2 in the presence of H2 O. Nanomaterials are produced from aqueous precursors containing low-cost metal salts and dispersed GO. Electron microscopy and other characterization methods show the decoration of the CGBs with sub-4 nm diameter binary and ternary alloy, non-oxide transition metal nanoparticles of controlled compositions. The nanostructures made by this process can potentially be used as electrocatalysts for fuel cells, electrodes in batteries and supercapacitors, conductive inks for printed electronics, catalysts in wastewater treatment, and many other applications where a graphitized carbon-metal nanomaterial is needed.